Corporate governance factors as predictors of earnings management. (January 2020) - Wasan, Pratibha; Mulchandani, Kalyani
Unlike developed markets, emerging markets like India have greater imperfections, have information asymmetry, and are particularly different in terms of accounting transparency, corruption, and corporate governance (CG). Also, concentrated ownership structure of Indian firms is more conducive for opportunistic earnings management (EM). There has been high incidence of financial frauds and EM in India particularly through related party transactions. The CG regulations were revised and enhanced in the year 2014 but increasing cases of financial frauds and CG violations indicate insufficiency of CG laws in the country. Linking CG to financial information in a context where investor protection laws are still evolving is important. The contributions of the present study are: first, it assesses earnings quality (EQ) as a key outcome of EM to confirm, in the Indian context, one of the two opposing perspectives of EM, namely opportunistic and informational. Second, it creates empirical evidence on those firm attributes and CG mechanisms which can predict EQ for investors in India. Third, it provides inputs on the effectiveness of the revised regulations in controlling EM, and finally, it puts forward theoretical rationale for EM and CG practices in India.